Daniel Balderston. How Borges Wrote. U of Virginia P, 2018. - Jeremy Glazier (Studies in 20th & 21st Century Literature, 2018)
Review of Daniel Balderston. How Borges Wrote. U of Virginia P, 2018.
Keywords: Borges; Balderston; Latin American Literature; Genetic Criticism